2015
DOI: 10.1039/c4ob02545h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the colour and chemical stability of model boranils: a strong effect of structural modifications

Abstract: A series of diarylborinic complexes with salicydeneaniline ligands bearing various functional groups at the 6-position have been synthesized in high yields by applying a straightforward one-pot multicomponent protocol. UV-Vis measurements revealed the influence of electronic character of substituents on the observed maximum of emission (λem). This has been confirmed by a relatively strong linear correlation (R(2) = 0.92) of λem with Hammett σp(+) constants. Such a correlation was investigated using a QTAIM ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 56 publications
(110 reference statements)
0
26
1
Order By: Relevance
“…As shown in Figure S11 (in the Supporting Information), we observed significant photobleaching for 1 – 3 under our experimental conditions whereas negligible changes were observed in the absorption spectrum of 4 upon irradiation, thereby indicating its excellent photostability. It is reported that boranils are prone to deboronation . On a similar note, the observed changes in the absorption spectra could be attributed to the elimination of the BF 2 moiety, resulting in the formation of the corresponding imines.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…As shown in Figure S11 (in the Supporting Information), we observed significant photobleaching for 1 – 3 under our experimental conditions whereas negligible changes were observed in the absorption spectrum of 4 upon irradiation, thereby indicating its excellent photostability. It is reported that boranils are prone to deboronation . On a similar note, the observed changes in the absorption spectra could be attributed to the elimination of the BF 2 moiety, resulting in the formation of the corresponding imines.…”
Section: Resultsmentioning
confidence: 53%
“…It is reported that boranils are prone to deboronation. [28,40] On as imilar note, the observed changes in the absorption spectra could be attributed to the elimination of the BF 2 moiety,r esulting in the formation of the corresponding imines. Furtherd etailed investigationsare necessary to ascertain the mechanism of this photochemical process.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…This includes, in particular, the work of Popelier who used a similarity measure in the form of a BCP (bond critical point) space to accurately predicted the Hammett σ p and σ m values for benzoic acids . Other more recent work has also provided QTAIM perspectives on Hammett constants …”
Section: Introductionmentioning
confidence: 99%